1985
DOI: 10.1051/animres:19850203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation de la consommation d'un troupeau de chèvres laitières sur parcours forestier — Méthode d'observation directe des coups de dents — Méthode du marqueur oxyde de chrome

Abstract: RésuméDeux méthodes d'estimation de la quantité de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
4

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 6 publications
2
15
1
4
Order By: Relevance
“…His results for January and April are somewhat higher, and for May even more so (75% compared to 30%), while for July they are low (3.6%) compared to this study (49.9%). In summer, bushes and trees made their greatest contribution to the diet, and this agrees with Morand-Fehr (1982), Meuret et al (1985) and Rosenberger and Meuret (1985) for similar regions.…”
Section: Trees and Bushessupporting
confidence: 86%
See 2 more Smart Citations
“…His results for January and April are somewhat higher, and for May even more so (75% compared to 30%), while for July they are low (3.6%) compared to this study (49.9%). In summer, bushes and trees made their greatest contribution to the diet, and this agrees with Morand-Fehr (1982), Meuret et al (1985) and Rosenberger and Meuret (1985) for similar regions.…”
Section: Trees and Bushessupporting
confidence: 86%
“…Following the technique described by Meuret et al (1985), six representative animals in the flock were selected for observation. The characteristics of the Florida breed, the description of the area where the experiment took place, methodology and management have all been thoroughly described in other studies (Sanchez-Rodriguez et al, 1993;Peinado-Lucena et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…La quantité de matière sèche ingérée (QI) par animal est donnée par la relation suivante (Meuret et al, 1985):…”
Section: Determination De L'ingestion Par La Methode D'observation DIunclassified
“…Therefore, feeding strategy and diet composition seems to have a definite impact on intake. Diet composition can be determined either by direct observation (Meuret et al, 1985) by rumen content analysis (Cordesse, 1994) Walters and Evans (1979) and Meijs et al (1982) as reported by Leaver (1985) ( (Cordesse, 1994) or biting observations on grazing animals (Meuret et a1,1985). None of them are perfect; they all introduce bias.…”
Section: Introductionmentioning
confidence: 99%